Reconstructing Female Language Teacher’s Roles from a Sociocultural Perspective (GIST – Education and Learning Research Journal, 2024)
The idea of teacher education has emerged to bridge the gap in questioning intellectual equality for both male and female teachers. Pursuing higher education in language professional careers which are understood as auxiliary jobs by male counterparts poses a big challenge for female teachers who were born and raised in a patriarchal community. This current study explored and interrogated socio-cultural contexts of learning and teaching by gender roles experienced by female language student teachers. It was designed as a narrative case study inviting three student teachers who currently pursued master’s or doctoral degree in the US to share their visual narrative experiences. The findings revealed any experience and aspiration of their language learning and teaching by oppression, stereotypes, and agency associated with female language teachers. Conclusions from this study will be helpful for student teachers to reconstruct their teaching philosophy and autonomy in family, school, and community settings.
Keywords: Female language teachers; EFL learning; Sociocultural theory; Feminism; EFL learning and teaching